Biocatalytic Isocitrate Production from Low‐Concentration Gaseous CO2 and Biobased 2‐Oxogultarate - Masamichi Hino; Yutaka Amao (Advanced Energy & Sustainability Research, 2025)
Isocitrate dehydrogenase (IDH) from yeast (EC 1.1.1.42) is an enzyme that catalyzes the decarboxylating isocitrate into 2‐oxogurtarate and carbon dioxide and the reverse process of the introducing carbon dioxide as a carboxy‐group to 2‐oxogurtarate to produce isocitrate via oxalosuccinate in the presence of co‐enzyme NADP+/NADPH. Thus, IDH is an attractive biocatalyst for carbon recycle technology based on the building carbon‐carbon bonds due to carboxylation of 2‐oxogurtarate with carbon dioxide. Enhancing the carboxylation of 2‐oxogurtarate by the addition of metal ions with carbon dioxide using IDH as a catalyst will lead to the establishment of biocatalytic carbon dioxide utilization. Especially, it is found that the addition of divalent manganese ion accelerates IDH‐catalyzed carboxylation of 2‐oxogurtarate with carbon dioxide. The direct use of carbon dioxide in the carboxylation of 2‐oxoglutarate catalyzed by IDH using the capture function of gaseous carbon dioxide in 4‐(2‐hydroxyethyl)‐1‐piperazineethanesulfonic acid (HEPES)‐NaOH buffer in the presence of manganese ion is attempted and a low concentration of gaseous carbon dioxide of about 5% is successfully used as a feedstock for isocitrate production.